Childhood Maltreatment and Mobile Phone Addiction Among Chinese Adolescents: Loneliness as a Mediator and Self-Control as a Moderator - Ma, Shutao; Huang, Yuhuai; Ma, Yankun (Frontiers in Psychology, 2020)
Previous studies have found that childhood maltreatment is an important risk predictor of adolescent mobile phone addiction (MPA). However, little is known about the mediating and moderating mechanisms underlying this association. Grounded in the basic psychological needs theory and the organism-environment interaction model, this study examined the mediating effect of loneliness and the moderating effect of self-control in the relationship between childhood maltreatment and adolescent MPA. A total of 981 Chinese adolescents (Mage = 13.68 years, SD = 0.92) completed measures regarding childhood maltreatment, MPA, loneliness, and self-control. After controlling for participants’ demographic variables, loneliness partially mediated the relation between childhood maltreatment and adolescent MPA and this indirect path was moderated by self-control. Specifically, the effect of loneliness on MPA was stronger for adolescents with lower self-control than for those with higher self-control. Our research provides additional evidence for the negative association between childhood maltreatment and MPA.